Inclusion of Children with Down Syndrome in Social Life: Parents’ Perceptions - Vanja Marković; Sandra Kadum; Sara Crvić (Interdisciplinary Description of Complex Systems)
Understanding the position, role and influence of the family, and especially parental perceptions, on the development of a child with Down syndrome is important both for planning support for the child itself and for developing opportunities for parent empowerment, so that they become and remain as stable and active as possible support for their child.